Relationship between Helicobacter pylori infection and metabolic syndrome - Işıktaş Sayılar, Emel; Çelik, Bülent; Dumlu, Şükrü (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To investigate the prevalence of metabolic syndrome (MS) and its components in patients with Helicobacter pylori that was detected using histopathological diagnostic methods. Materials and Methods: The study included 200 patients who presented with dyspeptic complaints and had indication for endoscopy. H. pylori-positive [HP (+)] and H. pylori-negative [HP (−)] patients were compared in terms of MS and its components. Results: The prevalence of H. pylori in general patient population is 49.5%. When patients were examined using a diagnostic criteria of MS, MS was present in 78 patients (78.8%) in the HP (+) (n=99) group and in 22 patients (21.8%) in the HP (−) (n=101) group (p<0.01). Logistic regression analysis revealed that H. pylori infection enhances the risk of developing MS by approximately 3.6 times (Relative Risk - (RR)=3.617, 95% CI: 2.465–5.307, p<0.001). With regard to the MS criteria, mean systolic–diastolic blood pressures and body mass index were significantly higher in HP (+) individuals than in HP (−) individuals. Furthermore, fasting plasma glucose, insulin and homeostatic model assessment–insulin resistance, very low-density lipoproteins, and triglyceride levels were also higher in the HP (+) group, whereas high-density lipoproteins levels were lower. Conclusion: H. pylori infection is a risk factor for MS. H. pylori leads to insulin resistance by developing chronic inflammation and accordingly facilitates the development of MS.